Persuasion Strategies Employed by Bell Clinton and Barack Obama in their Presidential Nomination Speeches in 1992 and 2008: A Comparative Study - جرادات، منيرة محمد (الجمعية الأردنية للعلوم التربوية, 2022)
تهدف هذه الدراسة إلى مقارنة استراتيجيات الإقناع التي استخدمها بيل كلينتون عام 1992 وباراك أوباما عام 2008 في خطابات الترشح للرئاسة الأمريكية في المؤتمر الوطني أمام أعضاء الحزب الديمقراطي في الولايات المتحدة الأمريكية. وقد تم الحصول على هذين الخطابين من موقع جريدة نيويورك تايمز وتم تحليلهم بطريقة تحليل الخطاب وبالتحديد منهج تحليل الخطاب النقدي من أجل بيان ومعرفة الاستراتيجيات التي استخدمها كل من كلينتون وأوباما لإقناع الناخبين من أجل التصويت لهما في الانتخابات الرئاسية الأمريكية. ولقد أشارت الدراسة إلى أن استراتيجيات الأقناع التي استخدمها كل من كلينتون عام 1992 وأوباما عام 2008 هي: استراتيجية الدمج (نحن مقابل هم)، استراتيجية إعطاء الوعود والالتزامات، استراتيجية المقارنة، استراتيجية المبالغة في إظهار الجانب السلبي عند "الآخر" واستراتيجية تكرار الجمل والكلمات. ويظهر التحليل أيضا أن كلينتون قام باستخدام ثلاث استراتيجيات أخرى لم يتم استخدامها من قبل أوباما وهي: استراتيجية التخويف، واستراتيجية الاقتباس من التاريخ واستراتيجية الاقتباس من النصوص الدينية. وبالمقابل استخدم أوباما استراتيجية إثارة العاطفة والتي لم تكن واضحة في خطاب كلينتون. وتوصلت الدراسة أيضا إلى أن كلينتون وأوباما لم يستخدما عددا من استراتيجيات الإقناع والتي يستخدمها السياسيون آحيانا من أجل إقناع الناخبين بآرائهم وبرامجهم مثل: استراتيجية إثارة النزعة الوطنية لدى الجمهور، استراتيجية طرح الأسئلة، استراتيجية الاستعارات التشبيهية، استراتيجية استخدام القسم، استراتيجية استخدام الأمثال الشعبية واستراتيجية التلخيص. وخلصت الدراسة إلى أن استراتيجيات الإقناع التي استخدمها كل من كلينتون وأوباما في خطابيهما قد أسهمت في فوزهما في الانتخابات الرئاسية الأمريكية لعامي 1992 و 2008. The study aimed at comparing the strategies of persuasion employed by Bell Clinton and Barack Obama in their presidential nomination speeches before the Democratic National Conventions in 1992 and 2008, respectively. The speeches were retrieved from the New York Times Newspaper website and were analyzed through a process of deconstruction to identify and compare the nature of persuasive strategies employed in each speech. The study applies the critical discourse analysis (CDA) approach in analyzing these speeches. The major strategies of persuasion which are usually used by politicians are reviewed to determine which of these strategies are employed in each of these speeches. The comparative critical deconstruction of the speeches showed that both Clinton and Obama employed a variety of persuasive strategies such as, the inclusive strategy, the strategy of giving promises and commitments, the contrasting strategy, the strategy of exaggerating the negative side of the “other” and the repetition strategy. In addition to these five major persuasive strategies, the analysis showed that Clinton in particular, employed three more persuasive strategies that were not used by Obama. These are: the fear strategy, the strategy of historical citation and the strategy of religious citation. On the other hand, Obama used only one strategy that was not clearly used by Clinton which is the emotional strategy. Furthermore, the analysis showed that other persuasive strategies which are sometimes used by some politicians were not employed by neither Clinton nor Obama in their speeches, such as the strategy of arousing the national identity of their audience, the questioning strategy, the metaphors strategy, the swearing strategy, the strategy of using proverbs, and the strategy of summarization. The study also concluded that the persuasive strategies used by Clinton and Obama in their speeches contributed to the winning of the presidential elections in 1992 and 2008.
Keywords: الخطب السياسية -- الإنتخابات الرئاسية -- اللغة الإنجليزية -- تحليل الخطاب -- وليام جيفرسون كلينتون، رئيس أمريكا -- باراك حسين أوباما، رئيس أمريكا